An assessment of the polytypic status of the Namib darkling beetles Onymacris unguicularis and Onymacris rugatipennis - Pollard, Rachel M. (My University, 2014)
The southern African beetle genus Onymacris (family Tenebrionidae) comprises 14 species, six of which are polytypic. Despite longstanding research on the physiological and behavioral adaptations of these desert beetles, little is known about their evolutionary relationships, particularly regarding the validity of currently recognized subspecies. In this study, I examined the polytypic status of the species Onymacris unguicularis and O. rugatipennis, each composed of two subspecies. The first, Onymacris unguicularis, is restricted to vegetationless dunes and is renowned for an unusual drinking behavior called fog basking. Northern populations—isolated from southern populations by approximately 300 km of duneless land—compose the subspecies O. u schulzeae, which exhibits only minor morphological differences from the southern subspecies, O. u. unguicularis. The second species, Onymacris rugatipennis, also contains two subspecies—O. r. rugatipennis and O. r. albotessellata—which are distinguished by the latter’s white wax bloom on the dorsum. Their ranges are contiguous and slightly overlapping, with O. r. rugatipennis occurring primarily along riverbanks and O. r. albotessellata occurring on dune bases. To assess the validity of the subspecies of O. unguicularis, I analyzed morphological variation in 35 specimens of O. u. schulzeae and 95 of O. u. unguicularis as well as mitochondrial DNA (mtDNA) sequence variation in five O. u. schulzeae and ten O. u. unguicularis. For O. rugatipennis, I examined only mitochondrial DNA sequence variation, generating sequence data for 11 O. r. rugatipennis and 12 O. r. albotessellata. Phylogenetic analysis of the mtDNA data revealed reciprocal monophyly between O. u. unguicularis and O. u. schulzeae, a pattern complementary to their morphological variation. On the basis of congruent phenotypic diversity, geographic delimitation, and genetic variation, I support the recognition of O. u. unguicularis and O. u. schulzeae as valid taxa. Conversely, the limited genetic divergence, absence of phylogeographic structuring, and number of shared haplotypes between O. r. rugatipennis and O. r. albotessellata suggest this species would be better regarded as a monotypic taxon.
Rachel M. Pollard is the winner of the 2014 Michael F. Bassman Honors Thesis Award
Keywords: Namib darkling beetles